La produzione dei formaggi a pasta filata. Tecniche semplificate per la prima mappatura dei rischi professionali legati all’ergonomia nel settore artigiano lattiero caseario / Production of “spun” cheese (mozzarella): application of the methodology of pre-mapping discomfort and/or risks in the dairy products craft industry - Maggiore, E. (La Medicina del Lavoro, 2011)
«Production of “spun” cheese (mozzarella): application of the methodology of pre-mapping discomfort and/or risks in the dairy products craft industry». Background and objectives: The aim of this study was to describe in detail the rules of application of the method of pre-mapping discomfort and/or risks (i.e. identification of sources of risk present in the production process) in craft industries of the dairy products sector and “spun” cheese “pasta filata” (mozzarella) production. Method: Application of the method proposed by Colombini et al. (1, 2) allowed identification of the main risks for workers in the dairy products trade. Results and conclusions: These risks mainly concern the muscular-skeletal apparatus (load handling, repetitive movements, pulling and pushing movements, posture) but are also due to uncomfortable microclimatic conditions and particular work organization. A more detailed study of the risk due to biomechanical overload of the upper limbs was made by applying the OCRA mini-checklist, a new tool available that was validated in comparison with the classic OCRA checklist. In addition, administration of the questionnaire on upper limb and spinal disorders, proposed by the EPM Research Unit, albeit with reservations considering the very limited sample size, showed a positive prevalence of shoulder disorders and the presence of minor disorders mainly of the lumbar spine.